Marketing - Tracy, Brian (Brian Tracy Success Library, 2014)
The success or failure of your business depends on the success or failure of your marketing efforts. If you can identify what your customers want, need, and can afford--and then give it to them--you will achieve outstanding results. Filled with Brian Tracy's trademark wisdom, this indispensable guide shows you how to build your customer base; set yourself apart from the competition; determine the correct price point; use market research and focus groups; make the most of distribution channels; master the concepts of specialization, differentiation, segmentation, and concentration; fulfill a ba
Keywords: Marketing